The Level of Readiness of Trainee Teachers for The Implementation of Inclusive Education in Primary Schools - Shahrul Asyraf bin Suhaimi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Inclusive Education Programme is an effort by the government in promoting education for students with special education needs especially in Malaysia. The implementation of the Inclusive Education Programme puts great pressure on mainstream teachers to prepare themselves to teach students with special educational needs. This study aims to identify the knowledge, skills and attitudes of trainee teachers towards the implementation of the Inclusive Education Programme in primary schools. The respondents were 59 trainee teachers who were pursuing study at the Institute of Teachers' Education Special Knowledge Campus. This survey study uses a quantitative approach through questionnaire instruments. The data obtained is analyzed using SPSS (Statistical Package for The Social Sciences) version 29 software. Researchers used the Theory of Constructivism and the Theory of Behaviorism in this study. The overall findings showed that the level of readiness of trainee teachers towards the implementation of inclusive education in primary schools in terms of knowledge, skills and attitudes is at a satisfactory level (mean 3.25; sp=1.14). This study has had implications for policymakers, trainee teachers and college training institutes. Among the recommendations of researchers in increasing the level of readiness of trainee teachers for the implementation of inclusive education is that by increasing their knowledge, skills and self-attitude in implementing inclusive education, policymakers in education should further diversify the teacher's professional development program on inclusive education to trainee teachers such as courses, workshops and training programs and the trainee teachers themselves need to increase their self-sufficiency in implementing inclusive education in elementary school.